Anterior Myocardial Infarction Associated with Myocardial Bridging in a Young Man - HA, Ngow; WMN, Wan Khairina (IIUM Medical Journal Malaysia, 2010)
A 43-year-old man presented with acute extensive anterior ST-segment elevation myocardial infarction. During coronary angiogram, a segment of myocardial bridging was noted in the mid-segment of left anterior descending artery. The association of myocardial bridging and an anterior ST segment elevation is rarely reported in the medical literature. Myocardial bridging is caused by systolic compression of a coronary artery by overlying myocardium tissue. It is a rare coronary artery anomaly, which usually has a benign prognosis despite some case reports of myocardial ischemia leading to myocardial infarction, lethal arrhythmias and sudden cardiac death. We report one such case of myocardial bridging that was complicated with acute extensive anterior myocardial infarction.